Endosidin1 defines a compartment involved in endocytosis of the brassinosteroid receptor BRI1 and the auxin transporters PIN2 and AUX1 - Robert, Stéphanie (National Academy of Sciences, 2008)
Although it is known that proteins are delivered to and recycled from the plasma membrane (PM) via endosomes, the nature of the compartments and pathways responsible for cargo and vesicle sorting and cellular signaling is poorly understood. To define and dissect specific recycling pathways, chemical effectors of proteins involved in vesicle trafficking, especially through endosomes, would be invaluable. Thus, we identified chemicals affecting essential steps in PM/endosome trafficking, using the intensely localized PM transport at the tips of germinating pollen tubes. The basic mechanisms of this localized growth are likely similar to those of non-tip growing cells in seedlings. The compound endosidin 1 (ES1) interfered selectively with endocytosis in seedlings, providing a unique tool to dissect recycling pathways. ES1 treatment induced the rapid agglomeration of the auxin translocators PIN2 and AUX1 and the brassinosteroid receptor BRI1 into distinct endomembrane compartments termed “endosidin bodies”; however, the markers PIN1, PIN7, and other PM proteins were unaffected. Endosidin bodies were defined by the syntaxin SYP61 and the V-ATPase subunit VHA-a1, two trans-Golgi network (TGN)/endosomal proteins. Interestingly, brassinosteroid (BR)-induced gene expression was inhibited by ES1 and treated seedlings displayed a brassinolide (BL)-insensitive phenotype similar to a bri1 loss-of-function mutant. No effect was detected in auxin signaling. Thus, PIN2, AUX1, and BRI1 use interactive pathways involving an early SYP61/VHA-a1 endosomal compartment.